A systematic overview of evidence for cognition‐oriented treatments in older persons: Dementia care research: Behavioral interventions. (7th December 2020) - Gavelin, Hanna Malmberg; Lampit, Amit; Hallock, Harry; Sabatés, Julieta; Bahar‐Fuchs, Alex
Abstract: Background: Cognition‐oriented treatments (COTs) – commonly categorized as cognitive training, cognitive rehabilitation and cognitive stimulation – are promising approaches for the prevention of cognitive and functional decline in older people. We conducted the first systematic overview of meta‐analyses investigating the efficacy of COTs on cognitive and non‐cognitive outcomes in older people with or without cognitive impairment. This presentation will describe the methodology, main findings, and implications from this overview and provide future directions for research and research synthesis in the field. Method: We conducted a systematic search to identify eligible reviews. Study characteristics, methodology and reported effect estimates were extracted and review quality assessed by two independent reviewers using AMSTAR 2. The effect estimates were summarized graphically to provide an overview of the available evidence across the different populations, interventions and outcomes. Meta‐regression was used to investigate the moderating effect of methodological variables on the overall effect estimate of cognitive outcomes. Result: The search yielded 51 eligible reviews, 46 of which were included in the quantitative synthesis. The confidence ratings were "moderate" for 9 (20%), "low" for 13 (28%) and "critically low" for 24 (52%) of the 46 reviews. While most studies provided pooled effect estimates for objectively measured cognition, non‐cognitive outcomes of potential relevance to patients and caregivers, such as clinical or functional status and caregiver burden, were more sparsely reported. The mean effect estimate on cognition was small for cognitive training in healthy older adults (Hedge's g 0.32, range 0.13‐0.64, 19 reviews), mild cognitive impairment (Hedge's g 0.40, range 0.32‐0.60, five reviews), and dementia (Hedge's g 0.38, range 0.09‐1.16, seven reviews), and small for cognitive stimulation in dementia (Hedge's g 0.36, range 0.26‐0.44, five reviews). Meta‐regression revealed that higher AMSTAR score was associated with larger effect estimates for cognitive outcomes. Conclusion: The available evidence supports the efficacy of COTs in improving cognitive performance in older people with and without cognitive decline. The extent to which such effects are of clinical value remains unclear, due to the scarcity of high‐quality evidence and heterogeneity in reported findings. For meta‐analyses in the field, there is a need for better adherence to methodological standards.